Social Media Marketing, Brand Awareness, dan Keputusan Pembelian: Studi Kuantitatif pada Produk Skincare Pria - Ikhsan Tyo Dewanggara; Halimah Zahrah (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The development of social media has changed consumer behavior in seeking information and making purchasing decisions, including for increasingly competitive men's skincare products. The high intensity of digital promotion gives consumers many brand choices, requiring companies to implement effective social media marketing strategies and build brand awareness to influence purchasing decisions. This study aims to analyze the influence of social media marketing and brand awareness on purchasing decisions for men's skincare products. This study uses a quantitative approach with a survey method. The research population consists of active social media users in Bandung who have used men's skincare products. The sampling technique uses purposive sampling with a sample size of 80 respondents. Data were collected through an online questionnaire using a five-point Likert scale and analyzed using multiple linear regression with the help of SPSS version 26. The results of the study indicate that social media marketing and brand awareness have a positive and significant effect on purchasing decisions, both partially and simultaneously, with brand awareness as the most dominant variable. This study concludes that optimizing marketing strategies through consistent and relevant social media can increase brand awareness and encourage consumer purchasing decisions.